The Relationship Between Cholesterol Levels and the Incidence of Preeclampsia in Pregnant Women at Gang Sehat Community Health Center - Yuni Nurisma; Imma Fatayati; Bagus Muhammad Ihsan; Ashfaque Raza Mikrani (Borneo Scientific Publishing, 2025)
Preeclampsia, a dangerous pregnancy complication characterized by elevated blood pressure (>140/90 mmHg), proteinuria, and edema, is a leading cause of maternal mortality. Various risk factors have been identified, including a history of hypertension, age, body mass index (BMI), parity, stress, knowledge level, dietary patterns, exposure to cigarette smoke, and lipid metabolism changes—particularly elevated cholesterol levels. This study aims to analyze the relationship between cholesterol levels and the incidence of preeclampsia among pregnant women at Gang Sehat Community Health Center, Pontianak City. Using a descriptive-analytic design with a cross-sectional approach and purposive sampling technique, the study involved 48 pregnant women with gestational age over 20 weeks during the period of May to June 2024. The results showed that 23 respondents (47.9%) had high cholesterol levels. Interestingly, all 17 respondents (35.4%) who experienced preeclampsia had high cholesterol levels. Meanwhile, among the pregnant women who did not develop preeclampsia, 6 respondents (19.4%) had high cholesterol levels, while 25 respondents (80.6%) had normal cholesterol levels. Statistical analysis using the Chi-Square test revealed a significant correlation between cholesterol levels and the incidence of preeclampsia in pregnant women, with an Asymptotic Significance value of < 0.001 (p < 0.05). In conclusion, there is a significant relationship between cholesterol levels and the incidence of preeclampsia in pregnant women at Gang Sehat Community Health Center, Pontianak City.